The Role of Audit Committees in Improving the Performance of Joint Stock Companies Listed on The Palestine Stock Exchange - Qabaha, Mahmoud Gawdat; Hamdan, Montaser (Journal of Economic, Administrative and Legal Sciences, 2022)
The study aimed at diagnosing and understanding the role of audit committees in improving the performance of public shareholding companies listed on the Palestine Stock Exchange. I assumed that there is no statistically significant relationship at the significance level (a < 0.05) between the role of audit committees in the field of "internal control", External Audit, Financial Reports and Improving the Performance of Public Shareholding Companies in Palestine). The study methodology and its descriptive and analytical design were chosen, and a questionnaire was designed that enjoys honesty and reliability to collect data from the participants in the study for statistical analysis. The study reached the results: the most important of which are: The Audit Committee discusses with the external auditor about any issues that may arise such as lawsuits, contingent liabilities, and accounting estimates. The audit committee meets with the external auditor at least once a year, and the study concluded several recommendations, the most important of which are: The necessity of directing the attention of the Palestinian Monetary Authority towards a clear definition of the conditions of independence that must be met by a member of the audit committee, as stipulated in the recommendations of the international committees that supported the formation of audit committees.